62-1/-9 METHODS FOR IMPROVING THE EFFICIENCY OF MULTI-CYCLONE TECHNOLOGY IN AIR PURIFICATION AND NEW APPROACHES - Davlatova, odina (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Multi-cyclone devices are widely used in industrial air purification systems, yet improving their efficiency remains a topic of continuous research. This article analyzes the methods and new approaches aimed at enhancing the efficiency of multi-cyclone technology. Several scientific solutions were explored, with their effectiveness supported by mathematical expressions. The findings show that significant improvements in air purification efficiency can be achieved through optimized designs and the application of new technologies. These improvements hold the potential to reduce energy consumption, improve particulate separation, and contribute to more sustainable industrial practices. The enhanced methods include the integration of electrostatic fields and the optimization of cyclone geometry. The integration of electrostatic fields accelerates the separation of particles, while the optimization of design trajectories ensures maximum particle separation. The results indicate that these approaches can lead to substantial gains in efficiency, thereby addressing key challenges faced by multi-cyclone systems in various industrial sectors.